Global conservation status assessment of the threatened aquatic plant genus Baldellia (Alismataceae): challenges and limitations - Kozlowski, Gregor; Rion, Stéphanie; Python, André; Riedo, Sébastien (Biodiversity and conservation, 2009)
In this study, the aquatic monocot Baldellia (Alismataceae) is used as a model for evaluating the general hindrances and shortfalls in the global conservation status assessment of a threatened taxon. Our study clearly shows that Linnean shortfalls (uncertainty in the number of species and taxonomy) and the Wallacean shortfall (fragmentary knowledge regarding distribution) form the basis for all other hindrances. We demonstrate that even in Europe, which has traditionally been very well investigated, between 60 and 75% of regions or countries possess no detailed distribution maps and/or data banks for Baldellia spp. Furthermore, between 50 and 60% of regions do not have any published red list category. Thus, only general conclusions concerning the global conservation status of the three Baldellia taxa are possible--a global assessment of conservation status for B. ranunculoides subsp. repens is nearly impossible. Baldellia ranunculoides s.str. shows a strong decline in practically all regions of its natural range, and thus it is probably the most threatened species in the genus. Baldellia alpestris is the least threatened species in the genus, even though it is a narrow endemic. Our case study clearly shows the need for reinforced coordination of research and conservation activities as well as an urgent need for data accessibility regarding taxonomic, chorological and conservation studies of endangered species.